Project-based learning in audiovisual translation: a case study in error analysis - Martins, Cláudia (2021)
As professors of audiovisual translation (AVT) in higher education institutions in Portugal, we have been concerned with the teaching of AVT, namely subtitling. In an attempt to prepare our students for the job market, we follow a constructivist approach, in line with Kiraly’s (2005) project-based learning. A dimension we cannot overlook in this context is the identification and analysis of subtitling errors, which we elaborate on according to Kuo (2014), Robert and Remael (2016) and Pedersen’s (2017) research. Thus, we chose a sample of nine films that were the target of our students’ projects from the last five academic years and pinpointed their errors, by following the analysis grid we put together for this purpose, which is based on temporal and spatial constraints, and stylistic, typographical and translation considerations. With this exercise in mind, we were able to conclude that segmentation and reading time of subtitles pose the greatest difficulty for our students.